Trading Costs, Liquidity, and Asset Holdings - Bhushan, Ravi (Review of Financial Studies, 1991)
In this article I develop a model that accounts for interdependence between trading costs in various asset markets arising from the optimizing behavior of liquidity traders. The model suggests that noise trading is an important determinant of the liquidity of asset markets and provides a positive theory for diversified asset holding by risk-neutral liquidity traders. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.